TEACHING BEGINNING READERS NARRATIVE OF PARENTS AS READING PARTNERS IN THE NEW NORMAL - Abella, Ma. Erika (International Journal of Arts, Sciences and Education, 2022)
In the new normal, parents have played a critical role in the development of reading skills of their children. Unlike teachers, not all parents are professionally trained to fulfill their duty as reading partners; hence, it is imperative to examine the narratives of parents as reading partners in teaching beginning readers. Using a qualitative research approach, the researchers unraveled the experiences of 10 parents who have direct involvement in teaching beginning readers in the new normal. The result disclosed that parents viewed their role as reading partners to be challenging. In motivating their children to read, they utilize positive reinforcement and impose punishment. Interestingly, they ensured that their children were assisted in reading by conducting reading sessions every day in a conducive place for learning. Notably, the Marungko approach and translation strategies were employed to help their children read. In the process, adequate educational background, setting of priority and time management, and availability of relevant reading resources enabled the parents to teach beginning readers. On the other hand, various household chores and the lack of background in teaching reading have fervently hindered the parents to perform well their role as reading partners. Ultimately, this study proves that parents are crucial in the development of reading skills among beginning readers and their narratives provide elucidation to their joys and struggles and what else may be done to empower them as reading partners in the basic education.